Nuclear magnetic resonance studies in a model transverse field Ising system - Nian, Y.-H.; Vinograd, I.; Chaffey, C.; Li, Y.; Zic, M. P.; Massat, P.; Singh, R. R. P.; Fisher, I. R.; Curro, N. J. (Frontiers in Physics, 2024)
The suppression of ferroquadrupolar order in TmVO 4 in a magnetic field is well-described by the transverse field Ising model, enabling detailed studies of critical dynamics near the quantum phase transition. We describe nuclear magnetic resonance measurements in pure and Y-doped single crystals. The non-Kramers nature of the ground state doublet leads to a unique form of the hyperfine coupling that exclusively probes the transverse field susceptibility. Our results show that this quantity diverges at the critical field, in contrast to the mean-field prediction. Furthermore, we find evidence for quantum critical fluctuations present near Tm-rich regions in Y-doped crystals at levels beyond which long-range order is suppressed, suggesting the presence of quantum Griffiths phases.